USM KAMPUS SEJAHTERA URGES STUDENTS TO BE MINDFUL OF GLOBAL CLIMATE CHANGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 14 April 2016 – The El Nino phenomenon is currently causing drastic climate changes which are affecting people’s lives and agriculture, especially in the context of Malaysia.